2016
DOI: 10.1111/all.13066
|View full text |Cite
|
Sign up to set email alerts
|

European Survey on Adverse Systemic Reactions in Allergen Immunotherapy (EASSI): a real-life clinical assessment

Abstract: AIT for respiratory allergy is safe, with a low number of SRs observed in real-life clinical practice. A personalized analysis of risk factors could be used to minimize SRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 36 publications
7
75
1
9
Order By: Relevance
“…11,14,196,197,198 Severe SRs with SLIT appear to be much less likely than with SCIT although the overall rate of any adverse reactions is similar in both SCIT and SLIT 14,184 (see Tables S2 and S3 in online supplement for details of classification 123,199 ). In a review of 66 SLIT studies (over 4000 patients who received over a million doses), there was 1 SR for approximately every 4 years of treatment and only 1 severe SR per 384 treatment years.…”
Section: Slitmentioning
confidence: 99%
“…11,14,196,197,198 Severe SRs with SLIT appear to be much less likely than with SCIT although the overall rate of any adverse reactions is similar in both SCIT and SLIT 14,184 (see Tables S2 and S3 in online supplement for details of classification 123,199 ). In a review of 66 SLIT studies (over 4000 patients who received over a million doses), there was 1 SR for approximately every 4 years of treatment and only 1 severe SR per 384 treatment years.…”
Section: Slitmentioning
confidence: 99%
“…In a recent meta‐analysis about the efficacy of grass pollen SLIT tablet by Di Bona et al., 7 treatment‐related adverse events requiring adrenaline were reported in the SLIT RCTs; however, no episode of anaphylaxis was reported. In recent real‐life clinical studies of AIT, less severe systemic reactions were reported with SLIT than with SCIT, although the overall rate of adverse reactions is similar in SCIT and SCIT . The safety profile for the present purpose is not regarded as being different from AIT for the treatment of AR.…”
Section: Ait For Prevention: Evidence and Clinical Recommendationsmentioning
confidence: 99%
“…Yet, a wide spectrum of side effects may occur due to the application of SCIT, ranging from mild local reactions to severe systemic anaphylactic reactions, potentially limiting its practical application . Concerning adult patients, multiple studies show diverging rates of systemic reactions, ranging from 2.4% to 50% of all patients and approximately 0.2% of all injections . The rare studies investigating systemic side effects in children indicate lower rates of <4% of all patients, respectively, <0.1% of all injections .…”
Section: Introductionmentioning
confidence: 99%